Insects, Oh Yes! - S. McCann; James D. Ellis; Michael K. O'Malley (EDIS)
ENY-1000, a 10-page illustrated fact sheet by S. McCann, J. D. Ellis, and M. K. O’Malley, is a general overview of insects, their importance, and their biology. It is designed as a supplemental elementary school curriculum for Grades 1-3, although it can apply to older or younger children as well. Published by the UF Department of Entomology and Nematology, December 2008.